Respiratory Muscle Strength and Exercise Performance in Cystic Fibrosis–A Cross Sectional Study - Sovtic, Aleksandar; Minic, Predrag; Markovic-Sovtic, Gordana; Trajkovic, Goran Z. (Frontiers in Pediatrics, 2018)
Introduction: Decreased respiratory muscle strength in patients with cystic fibrosis (CF) may cause progressive exercise intolerance during cardiopulmonary exercise testing (CPET), and may contribute to the development of chronic respiratory insufficiency. The aim of this study is to evaluate exercise tolerance during CPET of children and adults with clinically stable CF who exhibit different respiratory muscle strength. Methods: Sixty-nine clinically stable CF subjects aged 8 to 33 years underwent spirometry, body plethysmography, CPET, and respiratory muscle strength measurement. Respiratory muscle strength was measured using maximal inspiratory pressures (Pimax) and maximal expiratory pressures (Pemax). Participants were stratified into three groups according to Pimax values: below normal (≤80% predicted), normal (81-100% predicted), and above normal (>100% predicted). A similar stratification of participants was made according to Pemax values. The oxygen consumption on peak load (VO2peak) was expressed relative to BM (VO2peak/kg), relative to BM raised by the exponent of 0.67 (VO2peak/kg0.67) and as log-linear adjustment of VO2peak (VO2peak/kg-alo). Results: Participants with low Pemax values had a lower mean maximum load per kilogram/predicted (Wmax) (p = .001)VO2peak/kg (p = .006), VO2peak/kg0.67 (p = .038) and VO2peak/kg-alo (p = .001). There were no significant differences in exercise tolerance parameters with regard to Pimax values. Stepwise multiple linear regressions confirmed that Pemax (B = 24.88, β= 0.48, p < .001) was the most powerful predictor of Wmax. There were no statistically significant differences in age, lung function parameters, exacerbation score, or respiratory muscle strength according to gender. Conclusions: In subjects with clinically stable CF, expiratory muscle strength is associated with a decrease in exercise performance during CPET and can predict exercise intolerance. Increase in expiratory muscle strength by patient specific rehabilitation protocols would result in improvement of exercise tolerance.